Predictors of Peak Troponin Level in Acute Coronary Syndromes: Prior Aspirin Use and SYNTAX Score - Bhatt, Hemal A.; Sanghani, Dharmesh R.; Lee, David; Julliard, Kell N.; Fernaine, George A. (International Journal of Angiology, 2016)
The peak troponin level has been associated with cardiovascular (CV) mortality and adverse CV events. The association of peak troponin with CV risk factors and severity and complexity of coronary artery disease remains unknown. We assessed the predictors of peak troponin in patients with acute coronary syndrome (ACS). This study aims to determine the predictors of peak troponin in ACS. Cardiac catheterization (CC) reports and electronic medical records from 2010 to 2013 were retrospectively reviewed. A total of 219 patients were eligible for the study. All major CV risk factors, comorbidities, laboratory data, CC indications, and coronary lesion characteristics were included. Univariate and multivariate regression analyses were done. On multivariate linear regression analysis, ST-elevation myocardial infarction (p = 0.001, β = 65.16) and increasing synergy between percutaneous coronary intervention with Taxus and cardiac surgery (SYNTAX) score (p = 0.002, β = 1.15) were associated with higher peak troponin. The Pearson correlation between SYNTAX score and peak troponin was r = 0.257, p = 0.001. History of daily aspirin use was associated with lower peak troponin (p = 0.002, β = −24.32). Prior statin use (p = 0.321, β = −8.98) and the presence of CV risk factors were not associated with peak troponin. Coronary artery disease severity and complexity, urgency of CC, and prior aspirin use are associated with peak troponin levels in ACS. Our findings may help predict patient population with ACS who would be at a greater risk for short- and long-term CV morbidity and mortality due to elevated peak troponin.
Keywords: SYNTAX; troponin; acute coronary syndromes; aspirin; statin; STEMI; coronary artery disease; cardiovascular